2006
DOI: 10.1002/nvsm.40
|View full text |Cite
|
Sign up to set email alerts
|

How and why small to medium size enterprises (SMEs) engage with their communities: an Australian study

Abstract: SUMMARY/ABSTRACTWhile many studies address corporate philanthropy and corporate community involvement, limited work has been conducted internationally in small to medium businesses and even less has been elucidated about the Australian small business landscape. This article reports findings from qualitative research investigating giving to community causes by 52 small to medium size enterprises (SMEs) across Australia. Three key questions addressed in this article are: (1) why SMEs engage with community (2) ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 23 publications
1
63
0
3
Order By: Relevance
“…This personal experience with the arts organization appears at first to resonate with earlier literature discussing personal preferences of managers being influential (Brammer & Millington, 2004;Madden et al, 2006;Werbel & Carter, 2002). However, respondents from both sides of the dyad in each case appeared to view the advocate's knowledge more as information that contributed to the evaluation of the property.…”
Section: Advocates Have and Seek Knowledgesupporting
confidence: 72%
See 2 more Smart Citations
“…This personal experience with the arts organization appears at first to resonate with earlier literature discussing personal preferences of managers being influential (Brammer & Millington, 2004;Madden et al, 2006;Werbel & Carter, 2002). However, respondents from both sides of the dyad in each case appeared to view the advocate's knowledge more as information that contributed to the evaluation of the property.…”
Section: Advocates Have and Seek Knowledgesupporting
confidence: 72%
“…Some authors have found no evidence to suggest personal influence (Bartkus, Morris, & Seifert, 2002;Navarro, 1988), while other research suggests personal interests may play a role (Brammer & Millington, 2004;Campbell, Moore, & Metzger, 2002;Madden et al, 2006;Wang & Coffey, 1992;Werbel & Carter, 2002). In these later studies, the finger is typically pointed to the high level executive, such as the CEO (Brammer et al, 2006) or members of the board (Wang & Coffey, 1992).…”
Section: The Individual In Sponsorship Decisionsmentioning
confidence: 95%
See 1 more Smart Citation
“…As larger firms tend to have a bigger social impact, given the scale of their activities (Cowen et al, 1987), it is deemed equitable that the onus to be socially responsible also falls on them, rather than on small firms. Surprisingly, evidence suggests that many smaller firms tend to be involved in CSR activities in some way, particularly through donations and giving (Madden et al, 2006). The question, therefore, arises, what motivates such CSR participation by smaller firms, and moreover, is it economically justified?…”
mentioning
confidence: 96%
“…Out of these, the issue of firm size is identified as both vital and relatively unexamined (Madden et al, 2006). Firm size can affect strategic motivation, thereby having a positive effect on CSR participation (Adams and Hardwick, 1998;McElroy and Siegfred, 1985).…”
mentioning
confidence: 99%